2013
DOI: 10.1002/cmdc.201300048
|View full text |Cite
|
Sign up to set email alerts
|

MAO Inhibitory Activity of 2‐Arylbenzofurans versus 3‐Arylcoumarins: Synthesis, in vitro Study, and Docking Calculations

Abstract: Monoamine oxidase (MAO) is an important drug target for the treatment of neurological disorders. Several 3-arylcoumarin derivatives were previously described as interesting selective MAO-B inhibitors. Preserving the trans-stilbene structure, a series of 2-arylbenzofuran and corresponding 3-arylcoumarin derivatives were synthesized and evaluated as inhibitors of both MAO isoforms, MAO-A and MAO-B. In general, both types of derivatives were found to be selective MAO-B inhibitors, with IC50 values in the nano- to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 58 publications
1
31
0
1
Order By: Relevance
“…However, the rest of the studied compounds showed no activity against human MAO‐A. Previous docking studies suggest a more limited binding inside the A isoform for similar types of coumarins 23. Both enzyme isoforms showed some different residues in the pocket that can have an important impact in ligand selectivity.…”
Section: Methodsmentioning
confidence: 88%
See 2 more Smart Citations
“…However, the rest of the studied compounds showed no activity against human MAO‐A. Previous docking studies suggest a more limited binding inside the A isoform for similar types of coumarins 23. Both enzyme isoforms showed some different residues in the pocket that can have an important impact in ligand selectivity.…”
Section: Methodsmentioning
confidence: 88%
“…Since some of the synthesized derivatives exhibited good activity against hMAO‐B, we performed molecular docking calculations to predict the most stable poses of the ligands inside the protein binding site. To perform the modeling, we followed a similar protocol recently published by our research group22, 23 in which we used the crystallized structure of the hMAO‐B bound to 7‐(3‐chlorobenzyloxy)‐4‐carboxaldehyde‐coumarin ( c17 ) (PDB: 2V60) 24. A water molecule that establishes a hydrogen bond with the co‐crystallized ligand was retained in the pocket.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different research groups, including ours, have shown that coumarin is a privileged scaffold for the rational discovery and development of new h MAO‐B inhibitors (Figure ) and antioxidant agents . In addition to being very potent and selective MAO inhibitors, several leads previously reported by the group have proven to be reversible inhibitors . Moreover, hybrid molecules bearing the coumarin scaffold have been already reported by the group .…”
Section: Introductionmentioning
confidence: 84%
“…8 Some benzofuran derivatives are also known as monoamine oxidase and 5-lipoxygenase inhibitors, antagonists of the angiotensin II receptor, blood coagulation factor Xa inhibitors, ligands of adenosine A1 receptor, 5,9 and more recently as MAO inhibitors. [10][11][12][13][14] In general, benzofurans described as MAO inhibitors have a higher selectivity to the MAO-B isoform. In our efforts to contribute to the development of novel compounds that may be useful in the treatment of neurodegenerative disorders such as PD or AD, we are focusing on 2-phenylbenzofuran derivatives.…”
mentioning
confidence: 99%